Examining the Mediating Role of Job Satisfaction in the Relationship between Organizational Culture, Transformational Leadership, and Organizational Citizenship Behavior - Karina, Cinthya; Entang, Muhammad (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
.This study aims to examine the influence of organizational culture and transformational leadership on organizational citizenship behavior (OCB), with job satisfaction serving as a mediating variable. The study was conducted to understand how leadership style and workplace culture contribute to employee voluntary behaviors that support organizational effectiveness within the public sector. Using a quantitative explanatory design, data were collected from 120 civil servants working at the Regional Secretariat of Bogor Regency through a structured questionnaire. The research employed Structural Equation Modeling (SEM) using AMOS to analyze both direct and indirect relationships among variables. The results demonstrate that both organizational culture and transformational leadership have significant positive effects on job satisfaction and OCB. Moreover, job satisfaction was found to partially mediate the relationship between transformational leadership and OCB, indicating that leaders who inspire, motivate, and empower their employees enhance satisfaction, which in turn strengthens employees’ willingness to perform beyond formal job requirements. Similarly, a strong, adaptive organizational culture fosters a sense of belonging and shared responsibility, thereby improving extra-role behaviors.These findings underscore the importance of leadership transformation and cultural alignment in public organizations, where intrinsic motivation and teamwork are essential for achieving performance excellence. The study contributes to the existing literature by validating the mediating role of job satisfaction in explaining how organizational and leadership factors jointly influence discretionary work behavior in the context of local government institutions.